Septic Arthritis of Native Joints: Are Outcomes Better with Medical or Surgical Management?. (4th October 2017) - McConnell, Ian; Baghban, Adam; Holleck, Jurgen; Gupta, Shaili
Abstract: Background: There is limited evidence to support medical vs. surgical management of native joint septic arthritis (SA) with no established guidelines for care. Advantages of medical (antibiotics with or without serial needle aspiration) and surgical (arthroscopic or arthrotomic drainage) treatments are unknown. Methods: We conducted a single-center retrospective chart review of veterans diagnosed with SA over 10 years at the West Haven VA Hospital. Demographic, clinical, laboratory, imaging, and outcome data were extracted. Cases meeting inclusion criteria (positive culture or synovial fluid WBC >50, 000) were stratified by surgical vs. medical management. Evaluated outcomes included joint recovery, time to recovery, sterilization of synovial fluid, duration of antibiotics, length of stay, recurrence of SA, and mortality. Odds ratios were calculated by multivariate analyses for correlation of outcomes to risk factors and to management approach taken. Results: Sixty-one cases of SA met inclusion criteria. Average age was 67, 95% of patients were men, 89% White, 11% Black, 43% diabetic, and 43% had preexisting joint disease. 69% (41/61) of cases were managed surgically. Average length of stay for surgical group was 20 days compared with 14 days for medical group ( P = 0.28). Duration of antibiotics was longer in surgical group (60.3) than medical group (35.4), ( P = 0.09). S. aureus was the most common pathogen isolated (56%), followed by Streptococcus (11%) and gram-negative organisms (8%). Six (10%) patients had culture-negative SA. Mortality rate at 1 year was 3.2%. Full recovery of joint function at 1 year was achieved equally in both groups ( P = 1.0), by 15/20 medically managed (75%) and 31/41 surgically managed (76%), with no significant differences by pathogen. Full recovery at 3 months was noted in 10/20 (50%) medically managed vs. 8/41 (19.5%) surgically managed ( P = 0.02). Poor outcomes were not associated with joint location, pathogen, type of joint drainage, number of days to OR, or duration of antibiotics. Blacks had increased odds of poor outcome (OR 9.5; 95% CI 1.3–65.4). Conclusion: We detected no statistically significant difference in outcomes at 12 months between patients managed medically vs. surgically for native joint septic arthritis. Full recovery at 3 months was significantly higher among the medical group. Disclosures: All authors: No reported disclosures.